2008
DOI: 10.1152/jn.00940.2007
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic Release Probability Is Increased in Hippocampal Neurons From ASIC1 Knockout Mice

Abstract: Cho J-H, Askwith CC. Presynaptic release probability is increased in hippocampal neurons from ASIC1 knockout mice. J Neurophysiol 99: 426 -441, 2008. First published December 19, 2007 doi:10.1152/jn.00940.2007. Acid-sensing ion channels (ASICs) are H ϩ -gated channels that produce transient cation currents in response to extracellular acid. ASICs are expressed in neurons throughout the brain, and ASIC1 knockout mice show behavioral impairments in learning and memory. The role of ASICs in synaptic transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 62 publications
2
74
2
Order By: Relevance
“…Most modulators of ASIC1a function, including zinc, redox reagents, lactate, and PcTx1, act by altering the apparent proton sensitivity of the channel (16,18,25,(31)(32)(33)(34). These compounds also impact ASIC1a-induced neuronal death (8,9,15,31).…”
Section: Discussionmentioning
confidence: 99%
“…Most modulators of ASIC1a function, including zinc, redox reagents, lactate, and PcTx1, act by altering the apparent proton sensitivity of the channel (16,18,25,(31)(32)(33)(34). These compounds also impact ASIC1a-induced neuronal death (8,9,15,31).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that GABAergic inhibitory interneurons in the hippocampus have larger ASIC current densities than glutamatergic excitatory pyramidal neurons (PNs) (Bolshakov et al, 2002;Cho and Askwith, 2008;Ziemann et al, 2008). In line with this view, a recent report showed that ASIC1a null mice display delayed seizure termination after seizure induction and suggested that ASIC activation by falls in extracellular pH during seizures increases the cortical inhibition through preferential recruitment of GABAergic inhibitory interneurons (Ziemann et al, 2008).…”
Section: Introductionmentioning
confidence: 91%
“…In previous studies of hippocampal brain slices, extracellular field potential recordings suggested impaired hippocampal long-term potentiation (LTP) in ASIC1a −/− mice (20), although another study did not detect an effect of ASIC1a (33). Another study using microisland cultures of hippocampal neurons suggested that the probability of neurotransmitter release increased in ASIC1a −/− mice (32).…”
mentioning
confidence: 98%
“…Although these observations raised the possibility that protons might be a neurotransmitter, postsynaptic ASIC currents have not been detected in cultured hippocampal neurons (31,32), and whether localized pH transients might play a signaling role in neuronal communication remains unclear. In previous studies of hippocampal brain slices, extracellular field potential recordings suggested impaired hippocampal long-term potentiation (LTP) in ASIC1a −/− mice (20), although another study did not detect an effect of ASIC1a (33).…”
mentioning
confidence: 99%